2022
DOI: 10.1021/acsaem.1c03787
|View full text |Cite
|
Sign up to set email alerts
|

Improved Dye Regeneration through Addition of a Triphenylamine Electron Donor in Iodide-Based Electrolytes for Dye-Sensitized Solar Cells

Abstract: The addition of a small organic electron donor, tris(p-anisyl)amine (TPAA), to an iodide/triiodide electrolyte for dye-sensitized solar cells was found to give pronounced effects on charge transfer reactions. When using the organic dye LEG4 as a sensitizer, an improved solar cell performance was found, which could be attributed to the extremely rapid dye regeneration reaction when TPAA is added. In contrast, for the ruthenium dye N719, no significant solar cell improvement was found, despite rapid dye regenera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…This suggests that the efficiency of intramolecular electron transfer from the TAA moiety to Cor⋅ + in the DSSC with TAA‐AuCor is higher than that of the corresponding intermolecular electron transfer from TPAA to Cor⋅ + in the DSSC with AuCor + TPAA . Furthermore, the addition of TPAA can cause a decrease in the η ‐value due to undesirable charge recombination between the electrons in the CB of TiO 2 and the TPAA radical cation ( TPAA ⋅ + ) [37] . Therefore, the introduction of the TAA moiety by covalently tethering strategy clearly contributes to the higher η ‐value for the DSSC with TAA‐AuCor .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This suggests that the efficiency of intramolecular electron transfer from the TAA moiety to Cor⋅ + in the DSSC with TAA‐AuCor is higher than that of the corresponding intermolecular electron transfer from TPAA to Cor⋅ + in the DSSC with AuCor + TPAA . Furthermore, the addition of TPAA can cause a decrease in the η ‐value due to undesirable charge recombination between the electrons in the CB of TiO 2 and the TPAA radical cation ( TPAA ⋅ + ) [37] . Therefore, the introduction of the TAA moiety by covalently tethering strategy clearly contributes to the higher η ‐value for the DSSC with TAA‐AuCor .…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the addition of TPAA can cause a decrease in the η-value due to undesirable charge recombination between the electrons in the CB of TiO 2 and the TPAA radical cation (TPAA * + ). [37] Therefore, the introduction of the TAA moiety by covalently tethering strategy clearly contributes to the higher η-value for the DSSC with TAA-AuCor.…”
Section: Photovoltaic Performancementioning
confidence: 99%
See 1 more Smart Citation
“…8,23 Hence, integrating the features to enhance the dye regeneration process in the dye is a very attractive and important aspect, in addition to the built-in electronic and steric factors of the sensitizers. [24][25][26][27] Furthermore, in order to enhance the dye regeneration efficiency, the inclusion of triphenylamine-based additives in the electrolyte 28 and functionalization of the dye with bulky 3D-triarylamine donors have been reported. 29 Halogen bonding has been utilised in chemistry as well as in chemical biology due to its highly directional intermolecular interactions.…”
Section: Introductionmentioning
confidence: 99%
“…[ 13 ] Very recently, Ayaz et al reported that the addition of redox intermediate tris(p‐anisyl)amine (TPAA) to an iodide/triiodide electrolyte improved the dye regeneration, and thus enhanced its cell efficiency. [ 14 ] Nevertheless, since the presence of multiple species in the same solution, the application of the so‐called “tandem” electrolyte may lead to the intertwined problem of redox reactions, which is detrimental to the performance of the resultant device.…”
Section: Introductionmentioning
confidence: 99%